(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article describes the technology of cooking national boiled sausage, a unique dish of Uzbek cuisine, bliss for a true gourmet - this is (hasip) - homemade lamb sausage with liver. Despite its not very attractive appearance, the aroma is a real delicacy, the recipe of which can change slightly from personal preferences, while the main ingredients in hasip can always be varied, excluding them or adding them.